A Dynamic Study between Export from China to South Korea and Economic Growth in China - He, Yugang (Jurnal Ekonomi dan Studi Pembangunan, 2018)
Since the establishment of China and South Korea diplomatic relations in 1992, South Korea has become one of the most biggest trade partners for China. Therefore, this paper applies annual data from 1998 to 2016 to search for the dynamic operating mechanism between export from China to South Korea and economic growth in China. The vector error correction model is utilized to conduct an empirical analysis. The results indicate that there is a long-run relationship between them. Namely, if the export from China to South Korea increases by 1%, the economic growth in China will increases by 0.769%. Meanwhile, the result of Granger causality test also reveals that there is an unidirectional causality between them exists under 5% significance level. More importantly, the result of vector error correction mechanism shows that when the economic growth is derivate from the long-run equilibrium in the short run, it will return to the long-run equilibrium by 2.2%.Keywords:Â Economic Growth, Export from China to South Korea, Vector Error Correction ModelJEL Classification:Â C02, F10, F19